THE SAFETY PROJECT: SENTINEL-1 FOR THE MANAGEMENT OF GEOLOGICAL RISK - Barra, Anna; Monserrat, Oriol; Solari, Lorenzo; Herrera, Gerardo; Lopez, Carmen; Onori, Roberta; Reichenbach, Paola; GONZÁLEZ-ALONSO, ELENA; MATEOS, ROSA MARÍA; Bianchini, Silvia; Crosetto, Michele (WIT Transactions on Engineering Sciences, 2018)
SAFETY (Sentinel-1 for geohazards regional monitoring and forecasting – safety.cttc.es) is a two-year research project funded under the ECHO (European Civil Protection and Humanitarian Aid Operations) call “Prevention and preparedness projects in Civil Protection and marine pollution”, which started on the 1st January 2016. The mission of the project was to improve the efforts in detecting and mapping geohazards (i.e. landslide, volcanic and subsidence), by assessing their activity and evaluating their impact on built-up areas and infrastructure networks through space-borne radar data. This goal has been achieved through the use of Sentinel-1 DInSAR (Differential Synthetic Aperture Radar Interferometry) derived products and the development of software tools. The most challenging part concerned the semi-automatic generation of derived maps to be easily interpreted and exploited in the geohazard management by the Civil Protection Authorities, which are not usually familiar with DInSAR products. This work provides an overview of the project activities, describing the developed procedure, the main outcomes, and the most significant results obtained over the two test sites of the project: the Canary Islands (Spain) and the Volterra municipality (Italy). The main goal of this work is to present the potentialities of Sentinel-1 interferometry as a regular complementary input for the regional scale risk management.